(untitled) (Texas Journal of Medical Science, 2022)
Inorganic substances are represented by chlorides of sodium, potassium, calcium, magnesium, sulfates and phosphates. The main feature of the inorganic composition of pancreatic juice is a high concentration of bicarbonates, which create a pH of 7.5–8.8. Such an alkaline reaction ensures the neutralization of the acidic gastric chyme, the termination of the action of gastric pepsins and the creation of optimal conditions for the action of enzymes.pancreatic and intestinal juices. Organic substances are represented by enzymes. In the pancreatic juice contains all groups of enzymes that can carry out hydrolysis and proteins, and fats, and carbohydrates